The Effect of Gadget Use on Student Learning Outcomes in Civics Learning for Class V Elementary School - Suriani, Suriani; Basri, Muhammad; B, Rosleny (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the effect of using gadgets on student learning outcomes in Civics learning in Elementary Schools in Cluster VI, Pallangga District, Gowa Regency. This research was conducted in Cluster VI, Pallangga District, Gowa Regency. The research approach is quantitative. This type of research is a quasi-experimental control pretest-posttest design. The population in this study were all students in cluster VI, Kec. Pallangga. Sampling technique using random sampling. The sample in this study was class V SD Inpres Watu-Watu totaling 29 people as the experimental class and class V SD Negeri Taipale'leng totaling 28 people as the control class. This type of data collection uses pretest and posttest questions to measure student learning outcomes. The data analysis technique used is the analysis of the difference test / t-test which was previously tested for normality and homogeneity, The statistical results of the t-test of learning outcomes showed the value of sig. (2-tailed) of 0.002 <0.05 then the hypothesis is accepted. Thus, it can be concluded that there is an effect of using gadgets on student learning outcomes in learning Civics in Elementary Schools of Cluster VI, Pallangga District, Gowa Regency